2012
DOI: 10.1016/j.ajhg.2012.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Strikingly Different Clinicopathological Phenotypes Determined by Progranulin-Mutation Dosage

Abstract: We performed hypothesis-free linkage analysis and exome sequencing in a family with two siblings who had neuronal ceroid lipofuscinosis (NCL). Two linkage peaks with maximum LOD scores of 3.07 and 2.97 were found on chromosomes 7 and 17, respectively. Unexpectedly, we found these siblings to be homozygous for a c.813_816del (p.Thr272Serfs∗10) mutation in the progranulin gene (GRN, granulin precursor) in the latter peak. Heterozygous mutations in GRN are a major cause of frontotemporal lobar degeneration with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
387
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(394 citation statements)
references
References 33 publications
5
387
2
Order By: Relevance
“…We particularly considered variants close to splice sites and frameshift indels. Next, we prioritized the resulting variant list according to evolutionary conservation and filtered out regions with PhyloP [18] value<0.95; then retained variants predicted as "deleterious/damaging" by PolyPheN [19] and SIFT [20]. At last, we considered biological and clinical relevance of cerebellar ataxia for the identified candidates.…”
Section: Exome Sequencing Data Analysismentioning
confidence: 99%
“…We particularly considered variants close to splice sites and frameshift indels. Next, we prioritized the resulting variant list according to evolutionary conservation and filtered out regions with PhyloP [18] value<0.95; then retained variants predicted as "deleterious/damaging" by PolyPheN [19] and SIFT [20]. At last, we considered biological and clinical relevance of cerebellar ataxia for the identified candidates.…”
Section: Exome Sequencing Data Analysismentioning
confidence: 99%
“…Two homozygous GRN-deficient patients have been recently reported (30). These patients presented with adult onset neuronal ceroid lipofuscinosis (NCL), suffering from progressive loss of vision, retinal dystrophy, cerebellar ataxia, and seizures (Table 1).…”
Section: Homozygous Progranulin Mutation Causes Neuronal Ceroid Lipofmentioning
confidence: 99%
“…Patients with a homozygous mutation in the GRN gene present with neuronal ceroid lipofuscinosis (NCL), a group of neurodegenerative lysosomal storage disorders [12]. Additionally, Götzl et al (2014) recently revealed that FTLD patients due to PGRN deficiency have NCLlike pathology [13].…”
Section: Introductionmentioning
confidence: 99%